PLATFORM EMPLOYMENT IN UKRAINE LEGAL STATUS OF WORKERS AND PROSPECTS FOR LEGISLATIVE REGULATION - Чаленко, Поліна; Кайван, Олексій; Зіноватна, Іляна (SWorldJournal, 2025)
The article presents a comprehensive study of the legal status of digital platform workers in Ukraine and substantiates directions for improving national legislation in the field of platform employment. The relevance of the study is conditioned by the rap